(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
Evaporative resistance is an important parameter of clothing in its thermal comfort. The sweating thermal manikin developed for evaporative resistance test needs a textile skin covering its surface to simulate sweating. To investigate the effect of skin material on the measurement, three knitted fabrics (cotton, blend of cotton and polyester, polyester) were made into skins for the sweating thermal manikin Newton. The evaporative resistances of boundary air layer and four clothing ensembles were measured under an isothermal condition. It was found that the evaporative resistances measured with cotton skin were smaller than those measured with the other two skins. The large evaporative area and strong water absorbing ability of thick, dense and hydrophilic cotton skin result in more evaporative heat loss and consequently lower evaporative resistance values.